2022
DOI: 10.31579/2692-9392/147
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Approaches for Breast Cancer Metastasis to the Brain

Abstract: Breast cancer metastasis is a continued concern for patients with recent development in our understanding of disease progression. In this paper, we highlight the pathophysiology behind breast cancer metastasis. Blood brain barrier disruption plays a critical component in progression. We then investigate the current treatment strategies and recommended guidelines. This focuses on radiation and medical management. Finally, we address the role of surgical intervention. The data is organized into tables and figure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…These therapies include surgical resection, stereotactic radiotherapy, and whole brain radiotherapy. The approach chosen for treatment is individualized based on the extent and characteristics of the brain metastasis ( 37 , 38 ). For patients with endocrine-resistant breast cancer who develop brain metastasis and are resistant to most chemotherapies, surgical tumor resection and stereotactic radiotherapy have demonstrated efficacy in improving overall survival and reducing symptoms associated with brain metastasis, which remains crucial in optimizing outcomes for this population ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…These therapies include surgical resection, stereotactic radiotherapy, and whole brain radiotherapy. The approach chosen for treatment is individualized based on the extent and characteristics of the brain metastasis ( 37 , 38 ). For patients with endocrine-resistant breast cancer who develop brain metastasis and are resistant to most chemotherapies, surgical tumor resection and stereotactic radiotherapy have demonstrated efficacy in improving overall survival and reducing symptoms associated with brain metastasis, which remains crucial in optimizing outcomes for this population ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…47 Some studies have identified several potential biomarkers associated with BCBM, and their quantitative analysis may be a reliable indicator for evaluating the rationality of MRI imaging in BC patients with asymptomatic BM. 48 Brain MRI screening is only recommended when a patient has symptoms of suspected intracranial metastases, and the chances of early treatment of BM will be greater if closer brain monitoring can be performed when the patient has high-risk factors like visceral metastases. 27 Showing no difference with earlier issued data, 31,36 The security analysis of this research showed that the most usual untoward reaction was diarrhea.…”
mentioning
confidence: 99%